Westonci.ca makes finding answers easy, with a community of experts ready to provide you with the information you seek. Join our Q&A platform and get accurate answers to all your questions from professionals across multiple disciplines. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.
Sagot :
Answer:
g(-3) = [tex]\frac{17}{4}[/tex]
g(2) = -3
g(5) = [tex]-\frac{7}{4}[/tex]
Step-by-step explanation:
Let us solve the question
∵ g(x) = [tex]-\frac{3}{4}[/tex] x + 2, x ≠ 2
→ That means we can use it for any value os x except 2
∵ g(x) = -3, x = 2
→ That means we will use it only if x = 2
We want to find g(-3)
∵ x = -3 ⇒ ≠ 2
∴ We will use g(x) = [tex]-\frac{3}{4}[/tex] x + 2
→ Substitute x by -3
∵ g(-3) = [tex]-\frac{3}{4}[/tex] (-3) + 2
∴ g(-3) = [tex]\frac{9}{4}[/tex] + 2
∴ g(-3) = [tex]\frac{17}{4}[/tex]
We want to find g(2)
∵ x = 2
∴ We will use g(x) = -3
→ This is a constant function which means g(2) equal to -3
∴ g(2) = -3
We want to find g(5)
∵ x = 5 ⇒ ≠ 2
∴ We will use g(x) = [tex]-\frac{3}{4}[/tex] x + 2
→ Substitute x by 5
∵ g(5) = [tex]-\frac{3}{4}[/tex] (5) + 2
∴ g(5) = [tex]-\frac{15}{4}[/tex] + 2
∴ g(5) = [tex]-\frac{7}{4}[/tex]
Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Thank you for visiting Westonci.ca, your go-to source for reliable answers. Come back soon for more expert insights.